Exploring the Value of Philosophy in Curriculum Implementation in Physical Education: A Scoping Review - M. Luprandado , Rowen Jr.; Sazon, Pauline Jane C.; Agrano, Junique O.; Zapata, Kyla Marie C.; Gania, Mary Joy C.; Pansuelo, Chinie A.; Rodriguez, Maria Monica Y.; Fernandez , Paula Mae Q. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Educational philosophy provides a strong pillar of support and guidance to an institution. The scoping review aims to examine the significance of educational philosophies to curriculum implementation in Physical Education. The purpose was to provide a comprehensive overview of other relevant literature to identify gaps and observe existing cases related to this review. Additionally, it explores how these theoretical-based approaches influence the selection of content, teaching pedagogy, and preferred learning styles to deliver instructions effectively. Arksey and O’Malley’s (2005) five-stage framework was employed for a comprehensive and transparent process. Moreover, the study covered a criterion for inclusion and exclusion studies. The researchers selected articles from 1998 to 2024 that focused on the accuracy and consistency of the scope and material and underwent a rigorous evaluation to identify peer-reviewed papers. Further, the references list was manually searched and extracted from Google Scholar. The results indicate that educational philosophies are the common basis of reflection on how certain curriculum content should be properly implemented. Though learning contents might vary, teachers could still find an effective way to sustain the demands of learners providing substantial experiences in academic pursuit.